2021
DOI: 10.1088/1741-4326/abfadb
|View full text |Cite
|
Sign up to set email alerts
|

Bounds on edge shear layer persistence while approaching the density limit

Abstract: This paper details the theory of edge shear layer collapse as the density approaches the Greenwald density limit. It significantly extends earlier work, which was restricted in applicability. The zonal shear flow screening length is calculated for banana, plateau and Pfirsch–Schluter regimes. Poloidal field scaling persists in the plateau regime. Neoclassical screening and drift wave–zonal flow dynamics are combined in a theory, which is then reduced to a predator–prey model. Zonal noise, due to incoherent mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(30 citation statements)
references
References 68 publications
3
27
0
Order By: Relevance
“…The key point is that higher current strengthens zonal flow shear, for fixed drive. Since the edge is of primary interest in the context of DLs, we comment here that Singh & Diamond [33] also have shown that favourable Ip scaling of the asymptotic temporal response of the zonal potential persists in the plateau regime. In particular, the current scaling is the same, though the response is numerically smaller.…”
Section: Density Limit Scaling Theorymentioning
confidence: 87%
See 4 more Smart Citations
“…The key point is that higher current strengthens zonal flow shear, for fixed drive. Since the edge is of primary interest in the context of DLs, we comment here that Singh & Diamond [33] also have shown that favourable Ip scaling of the asymptotic temporal response of the zonal potential persists in the plateau regime. In particular, the current scaling is the same, though the response is numerically smaller.…”
Section: Density Limit Scaling Theorymentioning
confidence: 87%
“…These lead one to a new predator-prey model for turbulence-zonal flow evolution. Such a model was developed by Singh and Diamond in 2021 (hereafter SD1) by extending previous versions of the predator-prey model [33]. This model has features summarized in figure 14.…”
Section: Density Limit Scaling Theorymentioning
confidence: 99%
See 3 more Smart Citations